The Committee on Lands of the Conservation Commission, Canada, 1909-1921: Romantic Agrarianism in Ontario in an Age of Agricultural Realism - Bowley, Patricia (Scientia Canadensis)

(untitled) (CSTHA/AHSTC, 1997)
ABSTRACTThe Conservation Commission of Canada (CCC) was formed in 1909 as an advisory body to Liberal Prime Minister Wilfrid Laurier. It was divided into eight committees, each of which dealt with the management of a specific natural resource. The Committee on Lands (CL) was composed of members who were unable to accept or understand the changes in contemporary agriculture as it moved into the twentieth century. Dr. James Robertson, chair of the CL, was a staunch agrarian romantic, who believed that the most important attribute of agriculture was the moral, individual and spiritual benefit which it conveyed to the individual. The recommendations and projects of the CL were inappropriate and often outdated and redundant. Their endeavours were noted and appreciated by farmers, but their work had no lasting effect on agriculture in Ontario. The official concept of 'conservation', defined by the CCC, was based on efficient management of Canadian natural resources, including the soil. In reality, the CL interpreted conservation to mean the preservation of a vanishing rural lifestyle.